(untitled) (Research, Society and Development, 2021)
Two poultry houses were built on a small distorted scale and equipped with evaporative air conditioners. In one of the poultry houses, a cooling system was used to cool the water used in the evaporative system, while in the other, water in ambient conditions was used. Each poultry houses received 125 one-day-old Cobb chicks, which were raised up to 43 days old. During the period of the experiment, the environmental conditions of the two poultry houses were monitored: temperature and relative humidity and litter temperature. The surface temperature of the birds was also monitored. The final weight, the weight gain of the birds and the creative viability were evaluated. For air temperature, litter temperature, weight gain and final weight, there were no significant differences between the two poultry houses. The relative humidity was lower for the poultry houses that operated with water cooled in the evaporative air conditioner, which presented creative viability of 90.4%, while in that one that operated with water in ambient conditions, the creative viability was 86.4%.